Oral microbiome components predict response to neoadjuvant chemotherapy in triple-negative breast cancer patients - Fu, Xiaoyan; Huang, Ze; Li, Zongyan; Chen, Zuxiao; Wu, Zhijie; Yang, Qingyu; Li, Haiyan (Frontiers in Oncology, 2025)
The oral microbiome has emerged as a critical biomarker and regulator in cancer development and treatment response, garnering increasing attention from researchers. However, its specific role in breast cancer, particularly in triple-negative breast cancer (TNBC), remains poorly understood. The influence of the oral microbiome on chemotherapy sensitivity in TNBC, along with the underlying molecular mechanisms, remains unclear. Further investigation is needed to assess its potential as a biomarker for predicting chemotherapy sensitivity in this patient population. In the present study, significant differences in the composition of the oral microbiome were observed among patients with varying chemotherapy sensitivities for TNBC patients. Additionally, notable changes in the oral microbiome were noted after chemotherapy in patients with favorable responses to treatment. Our analysis revealed that chemotherapy-sensitive patients had higher levels of Lactobacillus and Neisseria species, alongside lower levels of Clostridium species. Post-chemotherapy, patients with positive responses demonstrated an increase in Clostridium and Microbacterium species, along with a decrease in Streptococcus and Neisseria. In contrast, no significant changes were observed in the microbiota of patients with poor chemotherapy responses. A classifier based on these microbial biomarkers yielded an area under the curve (AUC) value of 77.3% (95% CI: 60.5%-94.2%), supporting the potential of the oral microbiome as a predictive tool for chemotherapy sensitivity in TNBC. Given its simplicity, non-invasiveness, and repeatability, the oral microbiome holds promise as a valuable biomarker for predicting neoadjuvant chemotherapy sensitivity in TNBC patients.